Subsurface Drip Nitrogen Fertigation of Corn - A. Aubert; K. Roozeboom; D. Ruiz Diaz; A. Gipps; T. Wolf (Kansas Agricultural Experiment Station Research Reports, 2016)
The efficient management of nitrogen (N) fertilizer and irrigation is of utmost importance because they are two of the greatest expenses for corn production. This project was conducted to determine if yield and efficiency of fertilizer N in corn could be improved by applying N at later developmental stages through a subsurface drip irrigation (SDI) system. Experiments in 2014 and 2015 compared a Preplant Surface application that injected fertilizer in bands below the residue at planting, to four versions of SDI fertigation that differed in timing and total amount of N applied. The SDI Sidedress treatment concluded at corn tassel stage (VT). The SDI Maximum treatment supplied an additional 40 lb N/a through corn blister stage (R2). The SDI Sensor treatment received N fertigations after corn V10 stage only if the ratio of the SPAD readings from SDI Sensor plots to Reference plots was less than 95%. The Reference treatment received both the surface band injections and all SDI fertigations for total seasonal N application that far exceeded crop N requirements. The Reference treatment produced up to 32 bu/a more grain than the Preplant Surface treatment, but produced an average of 0.7 bushels of grain per pound of N fertilizer. The SDI Maximum treatment averaged only slightly less grain yield than the reference treatment but produced 1.15 bushels of grain per pound of N fertilizer on average. The SDI Sidedress and SDI Sensor treatments resulted in similar yields that averaged 16 bu/a more than the Preplant Surface treatment. The SDI Sidedress treatment used fertilizer N the most efficiently, producing 1.3 bushels of grain per pound of N fertilizer. Applying N into the reproductive stages of corn increased yield, but N fertilizer was used most efficiently when N applications were completed by VT. Although using the sensor to determine later N applications reduced fertilizer input slightly compared to a maximum fertilizer approach, yields were reduced enough to result in similar efficiency of fertilizer use.
Keywords: corn; fertigation; nitrogen fertility; subsurface drip irrigation